Study on the removal of Pb (II) ions from aqueous solution using chemically modified corn cob / Siti Raihan Zakaria ... [et al.] - Zakaria, Siti Raihan; Khazaai, Siti Norhafiza; Md Jan, Sarah Laila; Mat Hussin, Zurhana; Rozi, Nor Faizah (2013)
Corn cob, a by-product of agricultural industry that is easily available in nature and low cost has been investigated as adsorbent in order to remove the Pb (II) ions from aqueous solution. Corn cob has been chemically modified with carbon disulfide, CS2 through xanthation process to enhance the adsorption capacity of Pb (II) ions. Batch experiments were carried out for further study on the effect of parameters such as pH, adsorbent dosage. initial metal ions concentration and contact time. The adsorption kinetic data was well described by pseudo-second order model and the adsorption isotherm indicate that Langmuir model fitted well the experiment data than Freundlich model. According to the Langmuir model, the calculated value of maximum adsorption capacities of Pb (II) ions qmox was 16.39 mg g-1. The characteristic of corn corb before and after being treated with xanthate. CCX (corn cob xhantate) was characterized by Fourier transform infrared (FTIR) spectroscopy. This study showed that CCX can be used as good adsorbent materials for Pb (lI) removal from aqueous solution.